The Influence of Islamic Religious Education on the Social Attitudes of Students at MTs Al-Washliyah 48 Binjai - Purba, Fitriyadi; Purba, Muhammad Azam (Yayasan Rahmat Islamiyah, 2024)
This research aims to find out whether there is an influence of Islamic religious education on students' social attitudes. This research uses quantitative statistical data analysis research methods with the aim of testing predetermined hypotheses. The techniques used to collect data are questionnaires, observations and interviews, to analyze data by describing or illustrating the data that has been collected as it is without intending to create conclusions that apply to the general public or generalizations. The results of observations that have been made and the distribution of questionnaires given to students to measure the level of success of the Influence of Islamic Religious Education on Students' Social Attitudes at MTs Al-Washliyah 48 show a result of 83.67%, which is an interpretation of the results of the Influence of Religious Education. Islam can be said to be more than the minimum average score of 70%. So it can be concluded that the influence of Islamic religious education on students' social attitudes is true as proven by data that has been processed using SPSS media.